Numerical evaluation of strength in the Interface during Indentation spherical testing in thin films - Araújo, Rodrigo (2014)
The need for more components that are more resistant to wear and corrosion has promoted a growing interest in surface engineering. The search for improved tribological properties in materials contributes to the development of processes that extend the useful life of components and their applications in increasingly severe environments. In this respect, thin ceramic coatings have been used to enhance the tribological properties of components that operate under these conditions. However, new experimental assays are needed to assess the behaviour of these films and their surface as substrate. These experimental analyses require the use of sophisticated equipment and specialized personnel. On the other hand, with advances in computational mechanics, the application of numerical analysis to solve numerous technological problems has been increasingly frequent, owing to its low operational costs. This study aims to simulate an indentation assay with spherical penetrator in systems composed of thin ceramic film deposited on metallic substrate using a Finite Element commercial code. The main objective of this study was to evaluate the field behaviour of stresses in the contact region of the indenter with the sample, on the outline of the impression made by the penetrator and, primarily, on the film-substrate interface.